Highly efficient photocatalytic hydrogen evolution from water-soluble conjugated polyelectrolytes. (June 2019) - Hu, Zhicheng; Zhang, Xi; Yin, Qingwu; Liu, Xiaocheng; Jiang, Xiao-fang; Chen, Zhiming; Yang, Xiye; Huang, Fei; Cao, Yong
Abstract: Organic semiconductors for photocatalytic application have received wide attention recently. However, developing organic photocatalysts for highly efficient photocatalytic hydrogen evolution is a great challenge. Herein, we show highly efficient photocatalytic hydrogen evolution from a series of novel conjugated polyelectrolytes (CPEs) by modulating their interaction with co-catalysts. The water-soluble CPEs greatly enhance the photocatalytic performance with 50-fold improvement over that of their non-dissolved precursor conjugated polymer. More importantly, the photocatalytic activity of these CPEs can be optimized by regulating their interaction with Pt co-catalysts through molecular engineering on the side chain species and counterions of CPEs. The cationic CPEs perform better than anionic CPEs due to the robust interaction between quaternary ammonium side chains in cationic CPEs and Pt co-catalysts. It is found that the optimized interface contact between cationic CPEs and Pt co-catalysts can result in more efficient charge transfer and higher photocatalytic activity. Graphical abstract: Image 1 Highlights: A series of novel conjugated polyelectrolytes (CPEs) are dispersed into water to form nano-grade polymer micelles. CPEs enable much enhanced photocatalytic hydrogen evolution. The interaction between CPEs and Pt co-catalysts is well-regulated via their side chain species and counterions. The intimate interface contact between cationic CPEs and Pt co-catalysts enables more efficient charge transfer and separation.